PENGARUH BUDAYA ORGANISASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN MEDIASI KEPUASAN KERJA PADA PT. BPR SETIA KARIB ABADI SEMARANG - Arif Burhan; Ari Pradhanawati; Reni Shinta Dewi (Universitas Diponegoro, 2014)
The existence and success of an organization in achieving its objectives , can not be separated from the human resource factor . Human resources has a very important role in a variety of sectors , because the human resource is the key factor to mobilize other resources that exist in the company Once the importance of the role of human resources resulted in an organization should allocate some substantial funds for the improvement of human resources . To realize the desired goal , then one of them is to improve the performance of human resources in an optimal This study aims to analyze the influence of organizational culture and organizational commitment to employee performance on the job satisfaction with mediation PT . BPR Setia Abadi Carib Semarang . The population in this study were all employees of the BPR Setia Abadi Carib Semarang totaling 73 people , so this is a research study census . The analytical tool used in this study is a simple regression , multiple linear regression and path analysis . Based on the results of the analysis show the organizational culture , organizational commitment and job satisfaction has an influence on employee performance . Judging from the calculation of the coefficient of determination indicates that organizational culture , organizational commitment , job satisfaction variables were able to explain 78.8 % of the employee 's performance . where the coefficient of determination organizational culture has an influence of 70.1 % . 40.9 % of organizational commitment , and job satisfaction was 66.4 % , against the performance of employees . This shows that organizational culture has a greater impact and has a strong degree of closeness of relationship to the performance of employees . Based on the results of the data analysis we can conclude the influence of organizational culture , organizational commitment to employee performance on the job satisfaction with mediation PT BPR Setia Abadi Karib Semarang . Advice can be given in this study is to enhance and improve the commitment and job satisfaction can be done by giving priority attention to the work , provide rewards to employees in the form of direct flattery of superiors sehinngga employees will be proud of the job that can spur employees to work more optimal .